Tumor-infiltrating lymphocytes and macrophages as a significant prognostic factor in biliary tract cancer. - Ryota Tanaka; Shimpei Eguchi; Kenjiro Kimura; Go Ohira; Shogo Tanaka; Ryosuke Amano; Hiroaki Tanaka; Masakazu Yashiro; Masaichi Ohira; Shoji Kubo (PLoS ONE, 2023)
Background The impact of tumor-infiltrating lymphocytes (TILs) and tumor-associated macrophages (TAMs) on the prognosis of biliary tract cancer (BTC) is not completely understood. Therefore, in our study, we investigated the effects of the various immune cells infiltration in tumor microenvironment (TME). Methods A total of 130 patients with BTC who underwent surgical treatment at our institution were enrolled in this study. We retrospectively evaluated TILs and TAMs with immunohistochemical staining. Results With CD8-high, CD4-high, FOXP3-high, and CD68-low in TME as one factor, we calculated Immunoscore according to the number of factors. The high Immunoscore group showed significantly superior overall survival (OS) and recurrence-free survival (RFS) than the low Immunoscore group (median OS, 60.8 vs. 26.4 months, p = 0.001; median RFS not reached vs. 17.2 months, p < 0.001). Also, high Immunoscore was an independent good prognostic factor for OS and RFS (hazards ratio 2.05 and 2.41 and p = 0.01 and p = 0.001, respectively). Conclusions High Immunoscore group had significantly superior OS and RFS and was an independent good prognostic factor for OS and RFS.